Pengaruh Kombinasi Dosis Pupuk Kandang Kotoran Burung Puyuh dan NPK Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) Varietas Tosakan F1 - Rahmah, Alfi Khalifah; Muharam, Muharam; Surjana, Tatang (UNIVERSITAS LABUHANBATU, 2023)
Green mustard (Brassica juncea L.) is a vegetable plant that is much needed by the community. One of the factors causing the decline in mustard greens production is due to the community's need for mustard greens which is quite high along with population growth which continues to grow and the harvested area for mustard greens is decreasing. The development of mustard greens produced generally still uses inorganic fertilizers so that it is not yet oriented towards organic products or manure. Quail droppings can cause environmental pollution so that it becomes a solution to be used as manure. This study aims to obtain a combination of doses of manure, quail manure and NPK which gives the highest yield for the growth and yield of mustard greens (Brassica juncea L.) Tosakan F1 variety. The research was carried out in an experimental field located at Jalan DarmaBakti, Curug Village, Kiara Residence, West Bogor District, Bogor City. The research site is located at an altitude of 195 meters above sea level. The research took place from December 2021 to February 2022. The research method used was a single factor Randomized Group Design (RBD) consisting of 9 treatments and 3 replicates: A (Control), B (15 tons/ha of manure), C (250 kg /ha NPK), D (5 tons/ha manure + 200 kg/ha NPK), E (10 tons/ha manure + 200 kg/ha NPK), F (15 tons/ha manure + 200 kg/ha NPK), G (5 tonnes/ha of manure + 150 kg/ha of NPK), H (10 tonnes/ha of manure + 150 kg/ha of NPK) and I (15 tonnes/ha of manure + 150 kg/ha of NPK). Data were analyzed using the F-test analysis at the 5% level if there was a significant effect followed by the DMRT (Duncan Multiple Range Test) advanced test at the 5% level. The results of this study showed no significant effect of giving a combination dose of quail manure and NPK on the growth and yield of mustard greens (Brassica juncea L.) of the Tosakan F1 variety.Â Keywords: Mustard green variety Tosakan F1, quail manure fertilizer, NPK fertilizer.